2020
DOI: 10.31067/0.2020.249
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite Öğrencilerinin Obezite Farkındalıkları ile Beden Kitle İndeksleri Arasındaki İlişki

Abstract: Amaç: Araştırma, Kumluca ilçesinde öğrenim gören üniversite öğrencilerinin obezite hakkındaki farkındalıkları ile beden kitle indeksleri arasındaki ilişkinin değerlendirilmesi amacıyla planlanmıştır. Yöntem: Kesitsel türde yapılan bu araştırmada örneklem seçimine gidilmeden Akdeniz Üniversitesi Kumluca Meslek Yüksek Okulu'nda 2017-2018 eğitim ve öğretim yılı içerisinde öğrenim gören, çalışmaya katılmayı kabul 176 öğrenci dahil edilmiştir. Verilerin toplanmasında, Obezite Farkındalık Ölçeği (OFÖ) ve araştırmacı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 18 publications
0
4
0
2
Order By: Relevance
“…However, in more recent studies the prevalence of being overweight or obese in Turkey was much higher (51.7%) suggesting an increase in prevalence of obesity [19]. The percentage of students of normal weight (72.6%) in our study is similar to the results of Dülger and Mayda's study but considerably higher than those of Özkan et al [19].On the other hand, the percentage of our overweight or obese students is 12.7% (obese 2.2%; overweight 10.5%). The 2019 Turkey Health Survey reported that 21.1% of individuals over the age of 15 were in the obese category, also stated that 30.4% of women and 39.7% of men were overweight [20].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, in more recent studies the prevalence of being overweight or obese in Turkey was much higher (51.7%) suggesting an increase in prevalence of obesity [19]. The percentage of students of normal weight (72.6%) in our study is similar to the results of Dülger and Mayda's study but considerably higher than those of Özkan et al [19].On the other hand, the percentage of our overweight or obese students is 12.7% (obese 2.2%; overweight 10.5%). The 2019 Turkey Health Survey reported that 21.1% of individuals over the age of 15 were in the obese category, also stated that 30.4% of women and 39.7% of men were overweight [20].…”
Section: Discussionmentioning
confidence: 90%
“…Another study from Turkey in 2016 reported the prevalence of being overweight or obese as 27.5% in male and 21% in female students [18]. However, in more recent studies the prevalence of being overweight or obese in Turkey was much higher (51.7%) suggesting an increase in prevalence of obesity [19]. The percentage of students of normal weight (72.6%) in our study is similar to the results of Dülger and Mayda's study but considerably higher than those of Özkan et al [19].On the other hand, the percentage of our overweight or obese students is 12.7% (obese 2.2%; overweight 10.5%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 In Özkan's study, female's HEI scores were found higher than men, and there was no significant difference between gender and HEI score, similar to this study. 18 Looking at the HEI score categories, it was determined that 75,86% of male students and 77,0% of female students consumed a diet that needed improvement. In a study, when the classification of students according to the healthy eating index score (average 57,9±12,8 point) was examined; It was determined that 71,3% of male students is required to improve their diet quality.…”
Section: Resultsmentioning
confidence: 99%
“…Örneğin, Özkan ve arkadaşları da çalışmamızda olduğu gibi cinsiyet değişkeni ile obezite farkındalığı arasında anlamlı bir ilişki bulunmadığını ifade etmişlerdir. (Özkan, Adıbelli, İlaslan ve Taylan, 2020). Diğer bir araştırmada ise cinsiyet ile OFÖ puanlarının kadınlar lehine anlamlı farklılık olduğu bildirilmiştir (Acaroğlu ve Çolakoğlu, 2020).…”
Section: Discussionunclassified